voorbeeld 3

Rekenregels voor logartimen

Hoofdregel:
$
{}^g\log (x) = y \Leftrightarrow g^y = x
$

Hieruit volgt: $
g^{{}^g\log (x)} = x
$

Daarmee kan je de volgende regels aantonen:

$
\begin{array}{l}
{}^g\log (a) + {}^g\log (b) = {}^g\log (ab) \\
{}^g\log (a) - {}^g\log (b) = {}^g\log (\frac{a}{b}) \\
n \cdot {}^g\log (a) = {}^g\log (a^n ) \\
{}^g\log (a) = \large\frac{{{}\log (a)}}{{{}\log (g)}} \\
\end{array}
$

Voorbeeld 3

$
\begin{array}{l}
N = 3 \cdot 1,2^t \\
\log (N) = \log (3 \cdot 1,2^t ) \\
\log (N) = \log (3) + \log (1,2^t ) \\
\log (N) = \log (3) + t \cdot \log (1,2) \\
\log (N) = \log (1,2) \cdot t + \log (3) \\
benaderd: \\
\log (N) = {\rm{0}}{\rm{,079\cdot t + 0}}{\rm{,477}} \\
\end{array}
$

©2004-2021 Wiskundeleraar - login